Promotion through claiming centrality in L1 and L2 English Research Article Introductions - Abdi, Jalil; Sadeghi, Karim (International Journal of English Studies, 2018)
Marketization in all public spheres including academic discourse has led to the increased importance of promotion. One of the promotional tools usually used in Research Articles Introductions (RAIs) is claiming centrality which can be realized through different linguistic and textual resources. In this study, our aim was to explore differences between native and non-native writers in the use of strategies for claiming centrality in RAIs. To this end, a corpus of 50 RAIs (25 L1 and 25 L2 which were written by native English and non-native Iranian writers, respectively) was compiled and analyzed in terms of the strategies used for claiming centrality introduced by Wang and Yang (2015). The introductions were read through closely and the types and orientations of the strategies were identified. Then, the two sub-corpora were compared to highlight differences and/or similarities. The results showed that the mean occurrence of centrality claims in general is nearly the same in both groups of texts while in terms of the specific strategies employed to make such claims there are some differences between them. The findings of this study can serve EAP/ESP practitioners and learners as well as those wishing to publish their research internationally by raising their awareness in this regard and helping them report their research findings more convincingly.